ANALISIS FRAMING PEMBERITAAN AKSI TEROR MABES POLRI PADA MEDIA ONLINE KUMPARAN DAN TIRTO.ID - Mochammad Fauzan Amin; Muhammad Ramdhani; Oky Oxcygentri (Linimasa : Jurnal Ilmu Komunikasi, 2022)
The purpose of this study was to find out how the online media framing Kumparan and Tirto.id in reporting acts of terror at the National Police Headquarters. This study used qualitative research methods. Collecting data in this study using documentation techniques and literature study. The analysis technique uses Robert N. Entman's model framing analysis technique. The results of this research show that there are similarities between Kumparan and Tirto.id by defining terror acts at the National Police Headquarters as a form of terrorism attack. However, Kumparan emphasizes the human interest side of the perpetrators of the Police Headquarters attack by writing his name clearly and writing down the contents of the will left by the perpetrator. In addition, Kumparan also highlighted the actions of the police in this case, such as guarding and checking at the National Police Headquarters and shooting dead the perpetrators. Meanwhile, Tirto.id emphasizes the chronology of the terrorist acts at the Police Headquarters and also highlights the issue of terrorism itself by explaining the lone wolf and millennial terrorist phenomena. Kumparan and Tirto.id are trying to be as objective as possible in reporting the terror act at the National Police Headquarters.